The path of daggers - Jordan, Robert, 1948-2007 (Jordan, Robert, 1948-2007. Wheel of time, 1998)
The eighth installment in The Wheel of Time series follows familiar characters as they fight the forever invading Seanchan and continue to try and make peace and love amongst themselves.